2021
DOI: 10.1002/ajim.23241
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute myocardial infarction in the workforce: Findings from the Occupational Disease Surveillance System

Abstract: Background Increased risks of acute myocardial infarction (AMI) may be attributable to the workplace, however, associations are not well‐established. Using the Occupational Disease Surveillance System (ODSS), we sought to estimate associations between occupation and industry of employment and AMI risk among workers in Ontario, Canada. Methods The study population was derived by linking provincial accepted lost‐time workers' compensation claims data, to inpatient hospitalization records. Workers aged 15–65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 102 publications
(144 reference statements)
1
9
0
Order By: Relevance
“…These types of exposures may explain some of the findings in our study. Similar to other studies, a variety of transportation occupations were identified with higher rates of AMI 16,27 . Exposures in this industry could include long hours, sedentary behavior, and pollutants such as carbon monoxide and vehicle exhaust 27 .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These types of exposures may explain some of the findings in our study. Similar to other studies, a variety of transportation occupations were identified with higher rates of AMI 16,27 . Exposures in this industry could include long hours, sedentary behavior, and pollutants such as carbon monoxide and vehicle exhaust 27 .…”
Section: Discussionsupporting
confidence: 75%
“…Other groups have employed similar methodologies to investigate the association between AMI and work. A large study from Ontario also found that a variety of transportation occupations had elevated risks of AMI 16 . Similarly, they also found that female but not male chefs and cooks had an increased risk of AMI.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations